2011
DOI: 10.1364/oe.19.001767
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond dispersion control by extreme ultraviolet multilayer mirrors

Abstract: We report the first experimental demonstration of a-periodic multilayer mirrors controlling the frequency sweep (chirp) of isolated attosecond XUV pulses. The concept was proven with about 200-attosecond pulses in the photon energy range of 100-130 eV measured via photoelectron streaking in neon. The demonstrated attosecond dispersion control is engineerable in a wide range of XUV photon energies and bandwidths. The resultant tailor-made attosecond pulses with highly enhanced photon flux are expected to signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 34 publications
0
54
1
Order By: Relevance
“…56,57 The latter one is based on the different penetration depth inside the multilayer for different frequency components of the incoming light, so that a negative or positive chirp can be achieved to compensate the intrinsic chirp among the harmonics and further compress the pulse. 55,58 Based on this idea, aperiodic chirped multilayers were first designed with 52 the desired phase characteristics and for these designs an attosecond-level pulse duration was predicted. 57,59 With the advancement of the deposition techniques and various methods of phase measurements, significant progress has been achieved in chirped multilayer mirrors over the past few years.…”
Section: Broadband Multilayer For High Temporal Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…56,57 The latter one is based on the different penetration depth inside the multilayer for different frequency components of the incoming light, so that a negative or positive chirp can be achieved to compensate the intrinsic chirp among the harmonics and further compress the pulse. 55,58 Based on this idea, aperiodic chirped multilayers were first designed with 52 the desired phase characteristics and for these designs an attosecond-level pulse duration was predicted. 57,59 With the advancement of the deposition techniques and various methods of phase measurements, significant progress has been achieved in chirped multilayer mirrors over the past few years.…”
Section: Broadband Multilayer For High Temporal Resolutionmentioning
confidence: 99%
“…Pulse shaping techniques used in the XUV region have to be developed to control the full characteristics of the femto-or atto-second pulses. 38,58,[173][174][175] Development of some of these optics has begun, but there is much more to achieve which requires innovative solutions and much improvement of the deposition and nanofabrication technologies. Advancement of these high precision optics will enable and push forward a range of frontier techniques, like resonant inelastic x-ray scattering, 116 nanoscale spectroscopy, 176,177 ultrafast dynamics study, [178][179][180] and quantum control.…”
Section: Prospectsmentioning
confidence: 99%
“…Beyond that, this sort of spectrograms resembles the signal of frequency resolved optical gating devices (FROG) known from laser science (Trebino & Kane 1993); (Mairesse & Quéré 2005); (Justin Gagnon & Vladislav S. Yakovlev 2009). Since their origin is a cross-correlation of two unknown pulses recorded with a known response function (here the photoionization) adaptive algorithms can extract all relevant parameters of both pulses involved (Michael Hofstetter et al 2011). Such algorithms identify the temporal structure of the attosecond pulses and their temporal and spectral phase and thus fully characterize these light bursts that are the shortest signals that can be synthesized in the laboratory.…”
Section: Experiments and Applicationsmentioning
confidence: 99%
“…Aperiodic multilayer mirrors exhibit the required degree of freedom for tailored shaping of attosecond pulses in that energy range. Previous experiments have shown that multilayer mirrors can control the attosecond pulse dispersion slightly above 100 eV [5]. Extending this control into the "water window" spectral range requires multilayer optics of "atomic" precision since the spectral phase is extremely sensitive to even smallest thickness errors.…”
Section: Introductionmentioning
confidence: 99%